Factors associated with abdominal pain in patients submitted to colonoscopy - Bellei,Amanda Colpani (2017)
ABSTRACT Objective: The study evaluated factors associated with abdominal pain during colonoscopy. Methods: This was a cross-sectional observational study that evaluated patients who underwent colonoscopy between February 2014 and February 2015. Physical characteristics, surgical history and previous colonoscopies, indication and current examination conditions, fentanyl and midazolam dose, and pain level were analyzed. Significance level adopted: p < 0.05. Chi-squared test was used for association of categorical variables, Student's t-test was applied for comparison of means, and Spearman's coefficient was used for correlation. Results: A total of 566 women and 391 men with mean age of 54.81 years and mean BMI of 27,064 were evaluated. Of the total, 29 (3.0%) had mild pain, 42 (4.4%) had moderate pain, and 18 (1.9%) had severe pain. Women were less tolerant (p = 0.011) and had longer cecal intubation times (p = 0.001). Mean duration of colonoscopy and mean dose of midazolam were higher in patients with pain (p = 0.001), (p < 0.001*). Among the 39 patients with an incomplete examination, 8 reported pain (p = 0.049). Conclusion: Female gender and prolonged intubation time were significantly associated with abdominal pain during colonoscopy. Patients with discomfort had a higher failure rate on the exam. Additional doses of midazolam given to patients with pain were not effective.